2019
DOI: 10.1002/ece3.5288
|View full text |Cite
|
Sign up to set email alerts
|

Avian fitness consequences match habitat selection at the nest‐site and landscape scale in agriculturally fragmented landscapes

Abstract: Habitat selection theory suggests that when choosing breeding sites, animals should choose the best available habitat; however, studies show that individuals fail to choose habitats that maximize their fitness especially in drastically altered landscapes. Many studies have focused on selection at single scales, often using a single measure of fitness. However, links between habitat selection and fitness may vary depending on the spatial scale and measure of fitness, especially in situations where agricultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Understanding the effect of habitat quality on Florida scrub‐jay habitat preference, reproductive success, and survival is useful to inform adaptive management, especially to determine which successional state is needed for sustainable population growth (Breininger et al, 1995 , 2009 ; Breininger, Duncan, et al, 2014 ; Eaton et al, 2021 ; Johnson et al, 2011 ; Williams et al, 2011 ). Understanding such habitat effects at multiple spatial scales is generally important in species management, as management actions at nest sites (e.g., protect nest trees) might differ from management actions of territory condition or actions across a larger unit of landscape (Purcell & McGregor, 2021 ; Reiley & Benson, 2019 ; Routhier et al, 2020 ). Our results support a management objective that aims for a large proportion of strong territories because only strong had fecundity rates able to sustain populations taking all habitat‐specific mortality rates and nonbreeder effects into account (Lacy & Breininger, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the effect of habitat quality on Florida scrub‐jay habitat preference, reproductive success, and survival is useful to inform adaptive management, especially to determine which successional state is needed for sustainable population growth (Breininger et al, 1995 , 2009 ; Breininger, Duncan, et al, 2014 ; Eaton et al, 2021 ; Johnson et al, 2011 ; Williams et al, 2011 ). Understanding such habitat effects at multiple spatial scales is generally important in species management, as management actions at nest sites (e.g., protect nest trees) might differ from management actions of territory condition or actions across a larger unit of landscape (Purcell & McGregor, 2021 ; Reiley & Benson, 2019 ; Routhier et al, 2020 ). Our results support a management objective that aims for a large proportion of strong territories because only strong had fecundity rates able to sustain populations taking all habitat‐specific mortality rates and nonbreeder effects into account (Lacy & Breininger, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Understory vegetation is important for providing concealment cover from visual predators and foraging opportunities for poults (Randell 2003, Backs and Bledsoe 2011). The value of vegetation is likely distinguishable by birds at 2 scales (Reiley and Benson 2019): a coarser scale where overall 3‐dimensional structure provides cover in the form of concealment and shade (Rakowski et al 2019), and a finer scale where species‐specific understory communities affect locomotion and forage (Healy 1985, McCord et al 2014). Therefore, habitat selection of turkey broods may be affected by vegetation structure and composition but also availability of thermal refuge and arthropods; however, an optimal combination of these features may not concurrently occur at sites across the southeastern United States.…”
mentioning
confidence: 99%
“…Whooping Cranes ( Grus americana ) exhibit a mixture of generalist and specialist habitat selection behavior as well but they appear to be generalists among home ranges within regions and specialists among regions within biomes (Austin, Hayes, & Barzen, 2019). Reiley and Benson (2019) demonstrated that similar differences between fine and landscape scale selection was related to fitness in Bell's Vireo ( Vireo bellii ) and Willow Flycatchers ( Empidonax traillii ). Presumably, where scale of selection has strong influence on fitness, individuals will be more sensitive to changes in habitat conditions.…”
Section: Discussionmentioning
confidence: 99%